Scientific Research Supports in Higher Education Institutions - (:unkn) unknown (ILEM, 2017)
The purpose of this research is to examine the scientific research support (BAP) provided by academicians for the purpose of certain criteria. Descriptive screening model and content analysis technique were used in the study. The study's universe was 73 universities all of which were established before 2000. The study's sample included 30 universities accessible to BAP data. According to their findings, access to the activity reports of BAP units was easily achieved. When we look at the project type numbers, we see that it varies from 2 to 15. When we look at the types of supported projects; Supranational thesis projects, Infrastructure support projects for scientific research, Rapid support research projects, Participation and regulatory support projects for scientific activities are intensively encountered. The study found that universities accepted BAP support applications online and were able to accept applications at a high rate every year. In expenditure items, service purchase expenses, travel expenses, computer and staff expenses are encountered. When the BAP project duration is examined, it usually takes 12 to 24 months and results reports are requested. The support number limits range from 1-3. In the research results; we see that higher education institutions encourage academicians to scientific research projects, accept applications online and link them to commissions. Thus; the limit on the number of project supports leads the academicians to make one project every year or every two years.
Keywords: Higher Education Institutions; BAP Units; Scientific Research Supports